Commentary on: Solberg and Jensenius (2016) Investigation of ’intersubjectively embodied experience’ in a controlled electronic dance music setting - Greasley, Alinka E. (Empirical Musicology Review, 2017)
The motion capture study conducted by Solberg and Jensenius 2016 explores how people's movement on a dance floor is shaped by structural features of electronic dance music (EDM), with a particular focus on the breakdown and drop sections of tracks, the former being characterised by a reduction in musical texture and removal of the rhythmic bassline, and the latter when the rhythmic bassline re-enters and a thicker texture is re-established. The research also explored links between how the participants moved to the dance tracks and their experience of pleasure, and examined the extent to which dancing to EDM can be described as intersubjective. Results showed that the quantity of the dancers' movement reduced during the breakdown, and increased at the drop, as predicted. Ratings of enjoyment of the tracks, and qualitative reflections from the participants provided supporting evidence that the desire to dance increased at the moment of the drop, and that this was influenced by the movement of other people in the setting. In this commentary, I provide an overview of the authors' main arguments and critically evaluate the method and findings with suggestions for future studies.